Canada Goose Management Series: Capture and Euthanasia - Drake, David (Rutgers New Jersey Agricultural Experiment Station, Rutgers Cooperative Extension, 2004)
There is a wide range of non-lethal and lethal options available for Canada goose ( Branta canadensis ) management. This fact sheet, part of a series that examines goose management options currently employed, will present information on capture and euthanasia techniques that may be used to remove geese from your property. We define the technique and explore the advantages and disadvantages of capture and euthanasia in terms of, among other factors, amount of effort required to implement, effectiveness, and cost. Fact Sheet FS1029 Purpose: To provide information about managing Canadian geese by capture and euthanasia